2014
DOI: 10.1177/0255761413515818
|View full text |Cite
|
Sign up to set email alerts
|

Music without a music specialist: A primary school story

Abstract: This case study focuses on generalist primary (elementary) school teachers teaching music in an Australian school. With the onus for teaching music moving away from the specialist music teacher to the generalist classroom teacher, this case study adds to a growing body of literature focusing on generalist primary school teachers and music teaching. Previous literature largely focuses on these teachers self-reporting regarding their teaching of music. This case study aimed to identify what factors facilitate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 14 publications
3
46
0
3
Order By: Relevance
“…The immovable nature of these unmusical judgements can impact upon decisions taken regarding practice, in particular the extent to which teachers are willing to engage with music at all. For generalist primary practitioners, a belief that they are “unmusical” is often uncritically equated with a similarly categorical judgement regarding their (in)ability to teach the subject (de Vries, 2015). An expected lack of confidence in music generally can impact upon practitioners’ self-efficacy beliefs regarding the delivery of lessons (Holden & Button, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The immovable nature of these unmusical judgements can impact upon decisions taken regarding practice, in particular the extent to which teachers are willing to engage with music at all. For generalist primary practitioners, a belief that they are “unmusical” is often uncritically equated with a similarly categorical judgement regarding their (in)ability to teach the subject (de Vries, 2015). An expected lack of confidence in music generally can impact upon practitioners’ self-efficacy beliefs regarding the delivery of lessons (Holden & Button, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The challenges faced by many generalist primary teachers in relation to music education have been a recurrent issue across research, policy and practice (Stunell, 2006). A lack of confidence (de Vries, 2015; Holden & Button, 2006), performance anxiety (Abril, 2007) and insufficient training (Hallam et al, 2009; Hennessy, 2012) have been explored in research spanning several decades (Mills, 1989) and international borders (Russell-Bowie, 2009). Despite frequent debates within the field (Bowyer, 2012) and an avid quest for advocacy of the subject, little has changed “on the ground”, indicating that this is not a situation which will be resolved easily or quickly (de Vries, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La falta de conocimiento musical se cita a menudo como un problema para el profesorado generalista de Primaria. Este colectivo además del conocimiento musical necesita disponer de la confianza y las habilidades necesarias para enseñar esta disciplina (de Vries 2014). No obstante, existen estudios que demuestran que los adultos tienen capacidad para desarrollarse musicalmente a través de oportunidades que les permitan participar en la creación musical (Henley 2015), en lugar de concebir la habilidad musical como una entidad fija (Biasutti 2010).…”
Section: Formación Inicial De Docentes Desde La Educación Musical En unclassified
“…A study from 2009 of "preservice teacher training courses for primary classroom teachers across Australia found that, on average, approximately 17 hours was devoted to music within the degree program" (Parliament of Victoria, 2013, p. 126). Other issues for teachers include time constraint pressures indicative of the crowded curriculum (de Vries, 2015), high stakes testing and a lack of understanding of the value of music by educators and school leadership teams (Parliament of Victoria, 2013). There are no policy directives regarding the implementation of music education in primary schools (Parliament of Victoria, 2013), leaving education in music open for autonomous interpretation from school to school.…”
Section: Introductionmentioning
confidence: 99%